Star wars : Maul lockdown - Schreiber, Joe, 1969- (Del Rey, 2014)
To fulfill his do-or-die mission for the dark masters he serves, the dreaded Darth Maul must take on a bloodthirsty prison warden, a cannibal gang, cutthroat crime lord Jabba the Hutt, and an unspeakable alien horror in order to capture the ultimate weapon: an object that will enable the Sith to conquer the galaxy. Set before the events of Star Wars: Episode I, The Phantom Menace.